MULTIPLE APPLICATIONS OF COLD ATMOSPHERIC PLASMA IN MEDICINE - Aleksandra Przelaskowska; Jan Puliński; Karolina Wojdat-Krupa; Maksymilian Czarnota; Monika Rogowska; Klaudia Płudowska; Wiktoria Boral; Marek Dróżdż; Karol Sikora; Alicja Czyszczoń (International Journal of Innovative Technologies in Social Science, 2025)
Background: Cold atmospheric plasma (CAP) is a partially ionized gas produced at near-room temperature and atmospheric pressure. It has gained significant interest in recent years due to its diverse biomedical applications, especially in oncology, dermatology, and wound healing. The therapeutic potential of CAP is primarily based on the generation of reactive oxygen and nitrogen species (RONS), as well as minor ultraviolet radiation. Aim: The aim of this review is to summarize current knowledge from 2020 to 2025 regarding the biological effects and clinical applications of CAP, with particular emphasis on its role in cancer treatment, dermatological conditions, and wound management. Material and methods: A literature review was conducted using the PubMed database, focusing on articles published in English between 2016 and 2025 with a particular focus on recent evidence from 2021 to 2025 that address the medical use of CAP. Studies without full text, control groups, or of poor methodological quality were excluded. Results: In oncology, CAP demonstrates selective cytotoxic effects against tumor cells by disrupting cellular signaling, inducing oxidative stress, and modulating the tumor microenvironment. Studies report efficacy in cancers such as melanoma, breast cancer, and head and neck tumors. In dermatology, CAP exhibits antimicrobial activity, enhances skin barrier repair, modulates immune responses, and improves transdermal drug delivery. In wound care, CAP supports tissue regeneration by promoting cell proliferation, angiogenesis, and the breakdown of microbial biofilms. Conclusions: CAP is a promising tool in modern medicine with broad therapeutic potential. Despite encouraging results, further research is necessary to standardize treatment protocols, ensure long-term safety, and optimize plasma devices for clinical use.